Online Communities and the "un"-importance of e-Moderators - Puntschart, Ines; Tochtermann, Klaus (Proceedings of the International Conference on Networked Learning, 2006)
Within educational settings the use of social software often requires a time-consuming e-moderation, e.g. to keep discussions on a thematic track. This paper introduces a new methodology which helps to reduce the workload of e-moderators. To develop this methodology we present a community-communication model defining our problem space. Based upon this model we broaden our understanding about which effects are triggered by which actions of e-moderators. This leads to a set of "effect-equivalent" interventions associated to specific actions of e-moderators. Such "effect-equivalent" interventions reduce the workload of e-moderators as they can be taken without help of an e-moderator but result in the same effects as an explicit action of an e-moderator.